Incorporating Parents' Lived Experiences Into the Pediatric Audiology Course: A Qualitative Analysis of Student Reflections - Alanazi, Ahmad A; Nicholson, Nannette (American journal of audiology, 2024)
This study explores the underutilized pedagogical approach of incorporating lived experiences of parents with children possessing diverse hearing profiles and their family characteristics into the audiology curriculum for students. The aim was to investigate the impact of integrating such experiences into the classroom as an andragogical learning experience through the qualitative analysis of written student reflections. Twelve ( = 12) third-year female audiology students enrolled in a pediatric auditory (re)habilitation course attended a parent panel presentation during their regularly scheduled face-to-face class. Five parents of children with diverse hearing differences and diverse technology, communication, and educational choices participated on the panel as guest speakers via the Zoom platform. Students completed written reflections based on Rolfe's reflective framework. Written reflections were downloaded from Canvas and de-identified prior to uploading to NVivo software for coding, utilizing an inductive grounded theory coding strategy coupled with content analysis. This study underscores the effectiveness of written reflections as an effective andragogical learning model. Through reflective practice, students gained a deeper understanding of their experiences, values, and learning journeys, enhancing their competency in pediatric audiology and auditory (re)habilitation. Students articulated previous knowledge and learning experiences, utilized newfound insights from exposure to the parent panel of shared lived experiences, and connected this knowledge with future clinical applications. Key findings underscore the effectiveness of reflective practice as an andragogical learning model, facilitating the integration of prior experiences with new knowledge. Moreover, it aids the transition of the professional journey from the familiar to the unfamiliar, demonstrating the impact of combining real-world lived experiences to reinforce and highlight classroom topics. Additionally, reflective practice enhances professional efficacy by valuing patient/parent perspectives regarding clinical care and aligning with evidence-based principles.